1975
DOI: 10.1177/001872677502800604
|View full text |Cite
|
Sign up to set email alerts
|

nAchievement, nPower and Effectiveness of Research and Development

Abstract: The French Test of Insight was administered to 118 executives, scientists and engineers working on seventeen pharmaceutical and chemical industry R + D projects. Scoring was according to McClelland et al., nAch and Veroff nPow systems. The R + D projects were classified as successful and unsuccessful by outside experts, both from a technical and an economic point of view. Blind analysis showed that (1) nAch significantly correlated both with technical and economic success, (2) nPow was a strong factor making f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0
1

Year Published

1980
1980
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 7 publications
1
14
0
1
Order By: Relevance
“…Wainer and Rubin (1969) found that small high‐technology research and development firms headed by people high in achievement motivation showed significantly higher growth rates than other firms. In a study of Hungarian state‐owned chemical and pharmaceutical companies in Hungary during the years of socialist economic organization, Varga (1975) found a positive relationship between project success and the achievement motivation of the project staff. Finally, a meta‐analysis of 18 studies by Collins, Hanges, and Locke (2004) showed a mean correlation of .20 between implicit achievement motivation and entrepreneurship (see also Rauch & Frese, 2000).…”
Section: Background: the Achievement Motivementioning
confidence: 99%
“…Wainer and Rubin (1969) found that small high‐technology research and development firms headed by people high in achievement motivation showed significantly higher growth rates than other firms. In a study of Hungarian state‐owned chemical and pharmaceutical companies in Hungary during the years of socialist economic organization, Varga (1975) found a positive relationship between project success and the achievement motivation of the project staff. Finally, a meta‐analysis of 18 studies by Collins, Hanges, and Locke (2004) showed a mean correlation of .20 between implicit achievement motivation and entrepreneurship (see also Rauch & Frese, 2000).…”
Section: Background: the Achievement Motivementioning
confidence: 99%
“…There is considerable support for LMP theory, 37,92 -94 however an important qualification is that the relationship between LMP and leader effectiveness is more likely to be found at middle-and uppermanagement level, and in generalist rather than technical jobs. 37,95 For example, Winter 96 found that the effectiveness of people who held a high rank because of their technical or engineering skill was unrelated to LMP and was better predicted by n Achievement, presumably because performance in these jobs is more dependent on personal contribution than on the ability to influence other people.…”
Section: Motivation and The Stress-strain Relationshipmentioning
confidence: 99%
“…Such results suggest that general management requires persuasiveness and the desire to assert influence and exercise control over others. In contrast, technical managerial positions, such as those found in R&D, may require individuals with a high need for achievement attained through personal persistence (Varga, 1975).…”
Section: System Constraints and Fitmentioning
confidence: 99%